Work-related stress and mental well-being among police personnel in the Mangalore jurisdiction (International Journal of Occupational Safety and Health, 2025)
Introduction: Stress is the physiological response to any stimulus that requires mental or physical focus or exertion. Police officers are responsible for enforcing laws in their jurisdiction. As there is a rise in the personal risk of verbal and physical assaults, as well as ongoing involvement in a range of unpleasant situations, the duties of law enforcement officers tend to become fundamentally stressful. This research aims to assess work-related stress and mental well-being among police personnel in the Mangalore jurisdiction.Methods: A Descriptive study was conducted with 220 police personnel from the Mangalore Jurisdiction from March 3, 2023, to March 31, 2023. The Operational Police Stress Questionnaire and Warwick-Edinburgh Mental Wellbeing Scales were used to gather data from participants selected through a disproportionate stratified random sampling technique. To determine the relationship between police officers' mental wellness and their level of work-related stress, Karl Pearson's Correlation Coefficient was calculated.Results: 87.3% of the police personnel experienced high stress, followed by 10.5% who had medium stress, and 2.2% who had low stress. The majority, 59.6% of police personnel, had medium mental well-being, 35.9% had high mental well-being, and 4.5% had low mental well-being. The results also showed that there was no significant correlation (r = 0.034) between work-related stress and mental well-being among police personnel.Conclusion: This study concluded that there is a high level of work-related stress among police personnel in the Mangalore jurisdiction, which is directly or indirectly affecting their mental well-being.